Comparison of two combined drug therapy regimens for renal damage in patients with metastatic kidney cancer after previously performed unilateral nephrectomy - K. S. Titov; M. V. Epifanova; A. A. Alimov; O. Yu. Nesterova; E. V. Shutov; S. S. Lebedev; G. M. Zapirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Almost 450 new cases of renal cell carcinoma and almost 160 deaths from cancer are detected annually. Of particular interest to patients with metastatic renal cell carcinoma who often undergo radical nephrectomy prior to the appointment of combined immunotherapy is the assessment of further renal damage that occurs while taking tyrosine kinase inhibitors and immune checkpoint blockers.Objective: to compare renal damage in patients with metastatic RCC with a single kidney taking two drug therapy regimens: ipilimumab + nivolumab and pembrolizumab + axitinib. Object and methods. A retrospective study included 100 patients (73% men and 27% women) with metastatic renal cell carcinoma of the unfavorable prognosis group who had previously undergone unilateral radical nephrectomy for the underlying disease.  50 patients received ipilimumab + nivolubab combined immunotherapy, while 50 patients received pembrolizumab + axitinib. In these groups, CKD was observed in 83.0% and 77.3% of patients, respectively (80.2% of the total sample). Patients receiving pembrolizumab + axitinib were slightly older (median 63.0 years and 57.0 years, p = 0.019).Damage to a single kidney was assessed during 28-36 weeks of combination therapy, which corresponded to 12 drug injections in each group.Results. Acute renal injury (AKI) after the 1st administration of ipilimumab + nivolumab was observed in 10%, while after the 1st administration of pembrolizumao + axitinib - in 11% (p = 1,000). The maximum difference in AKI between the studied groups was noted after the 10th administration: AKI occurred in 25% and 6% of cases in the groups of patients receiving ipilimumab + nivolumab and pembrolizumab + axitinib, respectively, but the differences were also statistically insignificant (p = 0.513). Despite the older age of patients receiving pembrolizumab + axitinib, the average creatinine in the ipilimumab + nivolumab group was  43.0 mmol/L higher than in patients in the pembrolizumab + axitinib group (p < 0.001). Over the entire duration of therapy, urea in the ipilimumab + nivolumab group was 1.7 mmol/L higher (p = 0.010) than in the pembrolizumab + axitinib group with initially comparable parameters. The maximum difference in urea between the groups was observed after the 5th and 12th administration of the drugs, amounting to 2.6 mmol/l and 2.7 mmol/l, respectively (p = 0.009 and p = 0.032, respectively).Conclusion. Combined immunotherapy with ipilimumab + nivolumab in patients with metastatic RCC in patients with a single kidney has a more pronounced deterioration in renal function compared with combined immunotherapy with pembrolizumab + axitinib.